The Influence of Transformational Leadership on Organizational Performance: A Bibliometric Analysis - Sinthia, Ine; Haryono, Pauzan; Sugiarti, Diyah Yuli (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2024)
This study investigates the impact of transformational leadership on organizational performance through a bibliometric analysis. The aim is to understand how transformational leadership can address challenges faced by educational institutions, enhance innovation, and align practices with global trends while respecting the cultural values of Islamic education. Using VOSviewer software and data from Scopus and Google Scholar, this research systematically evaluates 77 articles published from 2014 to 2024. The findings highlight a significant increase in the literature on transformational leadership, with a focus on key leadership behaviours such as vision articulation, inspirational communication, and intellectual stimulation. These behaviours are strongly linked to improved organizational outcomes, including higher student enrolment in universities and greater institutional commitment. The study underscores the role of transformational leadership in fostering a positive, collaborative culture that encourages innovation and continuous improvement. The implications for educational leaders include the adoption of transformational leadership to improve organizational performance in response to evolving educational demands. Further research is recommended to explore the applicability of these findings in different educational contexts.